DISEASES PREDICTION SYSTEM USING MACHINE LEARNING AND HAND GESTURE - kumar, G.Manoj; Agrawal, Divyansh; C.Deepkiran, (International Journal of Psychosocial Rehabilitation, 2020)
Analysis of various symptoms and finally diagnosing the possible disease is an important issue nowadays. Apart from this , we have tried to solve the problems of physically challenged persons by accepting gestures which could be used for feature detection , extraction and finally matching with the clusters made.The image classification is supposed to be done using convolution neural networks. And the diseases prediction process is based on the well known machine learning algorithm such as DecisionTree,Naive Bayes and Random Forest and by using these algorithm diseases can be predicted more accurately even they have mostly the same symptoms and is also helps to get symptoms from disabled persons using Hand Gesture.